SiCepat Ekspress Service’s Quality Effect - Arvan, Eriyadi; Malinda, Okta; Ariska, Lisa (International Journal of Global Operations Research, 2022)
The effects of pandemic era are one of become an interest in conducting this research. The key factor for customers in making repeat purchases which is the largest portion of the company’s sales volume is customer satisfaction. The purpose of this study is to provide empirical evidence about the effect of service quality to customer’s satisfaction. This research was conducted at sicepat ekspress customer’s in negeri besar, waykanan lampung consisting of samples obtained as many as 100 customers. The type of data used in this research is primary data with the sampling technique used was purposive sampling. The data analysis method used is a quantitative method that the multiple regression analysis tested with Statistical Package for the Sosial Sciences (SPSS) V24. The results of this study indicate that service quality which consist of tangibles, realibility, assurance, integrity, benevolence, and competence have a significant positive effect on customer satisfaction. This results are expected to be useful to improve of service quality, especially at the sicepat ekspress company in indonesia.